2022
DOI: 10.1177/00048674221104411
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of self-reported mental illness among those imprisoned in New South Wales across three health surveys, from 2001 to 2015

Abstract: Objective: The prevalence of mental illness among those in prison is much higher than in the community; however, very few studies have examined whether rates have changed over time, in line with increasing self-reported rates in the community. Methods: This study compares the prevalence of self-reported mental illness, self-harm and suicidal thoughts/behaviours, and drug and alcohol use across three waves (2001, 2009 and 2015) of health surveys involving men and women in New South Wales prisons and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…followed by a comprehensive list of diagnostic labels (including mood, anxiety, psychotic, personality, and substance use disorders). The wording of the question and choice of a self-report measure of lifetime psychiatric diagnoses is consistent with previous research in prisoners (Binswanger et al, 2010;Browne et al, 2023). Participants were further asked about whether they used any illicit drugs (including nonprescribed psychotropic medications such as benzodiazepines but excluding tobacco and alcohol) during their current incarceration (Favril, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…followed by a comprehensive list of diagnostic labels (including mood, anxiety, psychotic, personality, and substance use disorders). The wording of the question and choice of a self-report measure of lifetime psychiatric diagnoses is consistent with previous research in prisoners (Binswanger et al, 2010;Browne et al, 2023). Participants were further asked about whether they used any illicit drugs (including nonprescribed psychotropic medications such as benzodiazepines but excluding tobacco and alcohol) during their current incarceration (Favril, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological evidence consistently indicates a substantially higher prevalence of mental disorders and psychological distress among people in prison compared with the general adult population (e.g., Baranyi et al, 2019; Bronson and Berzofsky, 2017; Butler et al, 2006; Fovet et al, 2020). One in seven prisoners worldwide has a severe mental illness (Fazel and Seewald, 2012), with data suggesting an increase in their mental health needs over the past decade (Browne et al, 2023; Butler et al, 2022). Although women only comprise a small proportion (7%) of the global prison population (Fair and Walmsley, 2022), research shows that female prisoners bear a higher burden of psychiatric morbidity compared with their male peers (Binswanger et al, 2010; Browne et al, 2023; Svendsen et al, 2023; Tyler et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A greater proportion of women reported substance use disorders across all surveys, in contrast to the general population where men have more than twice the rate of substance use disorder than women. 5,6 In the 2015 study, more than three-quarters of women reported at least one lifetime mental health diagnosis with almost twice the rates of all mental illness when compared to the men. Depression was seen in 61% of women, anxiety 51% and suicidal ideation in more than twothirds in the previous 12 months.…”
Section: Mental Illness In Imprisoned Womenmentioning
confidence: 99%
“…lack of clinician training and restrictive policies, as well as biases and limited cultural competence by healthcare providers (Clark et al., 2017). Trans people face these issues in addition to the stressors faced by all incarcerated people, with higher rates of substance use disorders, mental illness, self-harm, suicidal ideation and inadequate availability of mental healthcare in prisons (Browne et al., 2022; Fazel et al., 2016; Monasterio et al., 2020).…”
Section: Introductionmentioning
confidence: 99%